Comparing Survival between Peritoneal Dialysis and Hemodialysis Patients with Subclinical Peripheral Artery Disease: a 6-Year Follow-Up - Liu, Jiung-Hsiun (Ivyspring International Publisher, 2013)
Peripheral artery disease (PAD) is known to be an increased mortality risk in patients with end-stage renal disease (ESRD). The aim of this study was to compare patient survival between patients with subclinical PAD undergoing peritoneal dialysis (PD) and hemodialysis (HD). Subclinical peripheral artery was defined as an ankle-brachial index of less than 0.9. This study was conducted from April 2005, and the observation period ended on 30 June 2011. At the end of the follow-up, the status of all patients was assessed and data on mortality were obtained for the entire cohort. A total of 91 patients (61 HD and 30 PD) were included for analyses in this study. Mortality rate was 60.0% (18/30) for PD and 52.5% (32/61) for HD. Kaplan-Meier estimate demonstrate that PD patients had a higher mortality rate than those underwent HD (log-rank p = 0.0039). Cox regression model demonstrated that PD was an independent predictor for further mortality in ESRD patients with subclinical peripheral artery disease.(p = 0.012, HR: 1.776, 95% CI: 1.136-2.775). In multivariate analysis, the HD group still had a greater survival than PD group (p = 0.005, HR:1.916, 95% CI: 1.218-3.015). In patients with subclinical peripheral artery disease, the patient survival is better in HD patients as compared with PD patients.